Answer:
125
Step-by-step explanation:
Literally just add together
Answer:
ai
Step-by-step explanation:
y = 1
(0.4, 1)
(0.8, 1)
(1, 0.4)
(1, 0.8)
Answer:
the answer is A on edge
Step-by-step explanation:
Answer:
1,000g:60sec
or 10 gram every singular second.
Step-by-step explanation:
y=-4x+2
x-2y=23
Answer:
1. y = -4x + 2
Now, we can substitute this expression for y into the second equation:
2. x - 2y = 23
Substitute the value of y from equation 1 into equation 2:
x - 2(-4x + 2) = 23
Now, simplify and solve for x:
x + 8x - 4 = 23
Combine like terms:
9x - 4 = 23
Add 4 to both sides:
9x = 27
Divide by 9:
x = 3
Now that we have found the value of x, substitute it back into equation 1 to find y:
y = -4x + 2
y = -4(3) + 2
y = -12 + 2
y = -10
So, the solution to the system of equations is:
x = 3
y = -10
Answer:
The answer is x=5
A. 8.1
B. 10.9
C. 8.1 and 10.9
D. None of the above